Competitive Marketing Strategy Model Integrated with Artificial Intelligence for Grocery Store Business - Abdul Azis; Inayati Nuraini Dwiputri (IECON: International Economics and Business Conference, 2024)
Grocery stores are businesses categorized to Micro and Small Enterprises (MSEs) which have an important role in improving the global economy. The development of grocery stores in Indonesia has considerable potential for economic growth. The purpose of this study is to develop a competitive marketing strategy model that emphasizes aspects of artificial intelligence in an effort to realize business sustainability in the digital era nowdays. The sample used in the study was grocery stores in Dukuh Pakis District, Surabaya City. The model developed uses the ADDIE method which consists of five phases namely analysis, design, development, implementation, and evaluation. This study uses Usability Testing with task scenarios and questionnaires to achieve effectiveness, efficiency, and System Usability Scale (SUS) parameters to achieve satisfaction parameters. The result of this study is the design of a competitive strategy model as a marketing media that involves artificial intelligence technology that contains an use case diagram that involves the user interface design of the system. Therefore, existence of this marketing media can make it easier for grocery store owners to compete and achieve business sustainability in the digital era nowdays.